Dimensions of environmental and ecological economics - Sahu, Nirmal Chandra; Choudhury, Amita Kumari (Himayatnagar, India : Universities Press, 2005)
Contributed articles, with special reference to India.
Includes bibliographical references and index.
Keywords: Environmental economics; Pollution -- Economic aspects